Passing on negative interest rates - Georg Stadtmann; Karl-Heinz Moritz; Kristin Berthold; Tobias Stadtmann (International Journal of Management and Economics, 2020)
Since the ECB has lowered the interest rate on deposits into negative territory, more and more commercial banks are also passing on this negative interest rate to their customers. The main aim of this paper is to answer the question under which conditions the commercial banking sector will be more or less reluctant to pass the negative deposit rate on to its private customers. We first clarify the circumstances under which demand deposits and excess liquidity arise, and what role quantitative easing plays in this context. Within a game-theoretical framework, it is derived that the pressure to pass on the negative interest rate is particularly high if there are no switching costs, and the banking market follows a Bertrand competition.
Keywords: G21; E43; E52; 650; excess liquidity; penalty interest; game theory; investor behavior